The Impact of the Interface on the Perception of Trust of Older Adults Users When Using the Smartphone - Oliveira Camargo, Mayckel Barbosa de [UNESP]; Rino, Marcelo Valerio [UNESP]; Landim, Paula da Cruz [UNESP]; Sementille, Antonio Carlos [UNESP]; Gao, Q.; Zhou, J. (Springer, 2022)
The older adults, who were born and grew up in an analog era where digital technologywas not part of their lives, look with some suspicion on currently existing digital artifacts, such as the smartphone. This damaged trust relationship not only refers to the technology itself, but also to the way these older adults users interact with it. Thus, in this scenario, the interface is highlighted as a gateway to interaction for being, in most cases, responsible for the presentation and translation of systemic elements into graphic results that will serve as a subsidy for the entire cognitive process of the user. Based on this context, through the case study carried out with three users from exploratory research and qualitative questionnaires. The present work identified that visual representation on the graphic interface of apps has a direct impact, being negative or positive, on the trust relationship of older adults users in the using of the smartphone depending on their characteristics of real-world representation and facility of use.
Keywords: Older adults; Smartphone; Trust; UX